(untitled) (Revista científica Olimpia, 2020)
This research set as a goal to verify if there is a relation between cardio-respiratory capacity and the anthropometric patterns of 2319 students from fifth grade Elementary to fourth year High School in 25 school of the corporation Gabriel González Videla of the commune La Serena drawing from data produced by the diagnosis and monitoring fitness program implemented by the department of education of the corporation Gabriel González Videla. The results for the vo2 max – hip circumference variables showed a chi-squared of 242,068 with 12 degrees of freedom and a value of p < 0.05 a contingency coefficient of 0,307 of a possible max value of 0,816 which determines a moderate association among the variables. The vo2 max-BMI variables showed un chi-squared of 238,777 with 30 degrees of freedom and a value of p < 0.05 a contingency coefficient of 0,306 of a possible max value of 0,925 which can be summarized as a moderate association among the variables. The study concluded that there is a relation among the variables but this being rather moderate, anthropometric and physical condition evaluations must be developed due to the low relation among the variables.